Effects of plasticisers on the mechanical and physical properties of sodium alginate films - Ford-Barnett, Luke; Falagán, Natalia; Adams, Jessica M. M. (Elsevier, 2026)
Sodium alginate (SA) films show strong potential as biodegradable plastic alternatives because of their transparency, mechanical properties, and biodegradability. However, films composed solely of SA are limited in tensile strength and elongation properties. Incorporating biologically-sourced plasticisers can enhance these qualities, producing stronger or more stretchable films. In this study, selected plasticisers from distinct molecular classes (celluloses, polyols, carbohydrate sugars and oils) were combined with liquid SA, and the resulting formed films assessed for tensile strength, elongation, transparency at 600 nm, and thickness. Additionally, aliquots of SA-plasticiser solutions were dropped into calcium chloride to form insoluble beads, which were tested for water barrier properties. Overall, plasticisers improved SA film performance. Cellulose increased tensile strength, while polyols enhanced elongation but reduced tensile strength. Carbohydrates produced moderate improvements in both properties but to a lesser degree. Additions of plasticisers typically produced higher tensile strength or elongation properties compared to 2.5% (w/v) SA film alone (tensile strength 42.4 MPa; elongation to break 4.2%); for example, in SA films containing 10% (w/v) cellulose nanocrystals (tensile strength of 80.5 MPa); or in SA films containing 2% (w/v) fructose and 4% (w/v) xylitol (elongation to break 137.0%). All films were below the maximum thickness threshold for plastic classification (<0.25 mm), confirming uniformity and suitability for future applications. These findings highlight the potential of multi-plasticiser formulations to enhance the mechanical and barrier properties of SA films, supporting their development as sustainable, comparable alternatives to petroleum-derived plastics.
Keywords: 40 Engineering; 4016 Materials Engineering; 3108 Plant biology; 4004 Chemical engineering; Biodegradable; Elongation; Macroalgae; Plasticiser; Seaweed; Tensile strength